Scada Pada Proses Destilasi Dengan Pengendalian Suhu Menggunakan PID - Dasa Novfowan , Anang; Mieftah , Mochammad; Kusuma, Wijaya (Elposys: Jurnal Sistem Kelistrikan, 2024)
Controlling temperature is crucial because it is the most significant factor in the distillation process. Temperature instability is a result of manual and traditional control, and several errors may occur. Therefore, the low quality of the product that is produced during the distillation process has an additional effect. In order to effectively control or manage the system, an automatic temperature control system is designed using an electronic controller with a closed system control mode that not only delivers setpoint values but also feedback.The procedure of distillation that is being employed involves combining two different kinds of solutions: water and ethanol, which has a boiling point of 78°C.Thermocouple sensors are used to monitor temperature, and PLCs with PID control are used to process the temperature data that are obtained. For plant supervision, control, and data collecting, a SCADA is necessary. A number of tests have been conducted, including near loops with and without PID that are SCADA-monitored. The temperature stability response is then examined by analyzing the outcomes of multiple tests that have been conducted. Values of Kp = 5188, Ti = 182, and Td = 457 were found by using the Ziegler Nichols method to the temperature control of the distillation equipment. Furthermore, the steady state error was no more than 1% and the overshoot characteristics were only 2.5%, according to the system response graph.. From the Ziegler Nichols PID control parameters, it shows a good system response and produces ethanol distillation results with a concentration of 88%.